PEMBUATAN APLIKASI BERBASIS WEBSITE TOKO ONLINE MAZHAB CREATIVE MENGGUNAKAN PHP DAN MYSQLSITE - Rani Puspita; Rina Astriani (Jurnal Ilmiah Teknik, 2025)
The rapid development of information technology is encouraging businesses to transform towards digital. Toko Madzhab Creative, as a small and medium business in the field of t-shirt screen printing and sticker printing, faces challenges in increasing efficiency and market reach. This research aims to develop a user-friendly website to simplify the ordering process and increase sales. In creating the Creative Mazhab Shop website, the SDLC method was used, namely by designing, building and testing a PHP and MySQL based website. The research results show that the website developed has succeeded in increasing the efficiency of the ordering process and has the potential to increase sales and market reach of the Madzhab Creative Store. This website can be accessed at https://mazhabcreative.online.